Structural alterations of the thymus in high-risk fetuses and their relationship with obstetric conditions and fetal congenital defects - Lisset Ley Vega; Yanna Chao Martínez; Aimé Rosario Benítez Molina; Jesús Arturo Satorre Ygualada; Fidel Ernesto Pérez Marrero; Mery Karla Satorre Ley (Acta Médica del Centro)
Introduction: the thymus is a fundamental organ in the development of immunity, its interest has increased in recent years with the development of high-resolution ultrasound. Objective: to determine the relationship between structural alterations of the thymus in high-risk fetuses with obstetric conditions and fetal congenital defects. Methods: a cross-sectional descriptive study was carried out during the period from September 2019 to May 2023. We worked with the total number of pregnant women (382) seen in the prenatal fetal echocardiography consultations belonging to the Province of Villa Clara. A thymic ultrasound was performed that included area, anteroposterior diameter, transverse diameter, and the thymus-thorax ratio. Results: the predominant risk factor was the image of suspected fetal congenital heart disease on screening ultrasound (36.65%). There were significant differences in the average ranges of the thymus-thorax index in the groups that were compared. 61.78% of patients without obstetric conditions had fetuses with normal thymuses. When analyzing the behavior of obstetric conditions with the presence or not of the structural alteration of the thymus, preeclampsia occupied the highest percentage (55.56%). Fetuses that presented congenital defects represented 18.59%, 26.09% with structural alteration of the thymus. Conclusions: measurement of the thymus using the thymus-thorax index provides useful information about possible fetal conditions and constitutes a diagnostic tool for better assessment and monitoring of pregnant women at risk of preeclampsia and intrauterine growth restriction.